2021
DOI: 10.1021/acsami.1c03098
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic C–H Activation with Alcohol as a Hydrogen Atom Transfer Agent in a 9-Fluorenone Based Metal–Organic Framework

Abstract: Hydrogen atom transfer (HAT) has become an attractive strategy for the activation of hydrocarbon feedstocks. Alcohols, as inexpensive and efficient hydrogen transfer reagents, have limited application in C–H functionalization due to the difficulty in the alkoxy radical acquisition. 9-Fluorenone moieties were incorporated into the metal–organic framework (MOF) as a photocatalyst; through the formation of hydrogen bonds between the carbonyl group of a ligand and alcohol, alkoxy radicals could be obtained by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 72 publications
(83 reference statements)
1
16
0
Order By: Relevance
“…Principally, the low resistance and small arc radius in the EIS-Nyquist plot imply fast charge transfer in the semiconductor, and the experimental results showed that the resistance of Cu-MOF was greatly reduced under light illumination conditions (Figure c). Furthermore, the transient photoluminescence spectra demonstrate the stronger separation efficiency of Cu-MOF for photogenerated electron and hole pairs (Figure d), which further explains the properties of Cu-MOF as a well-performing photocatalyst. , …”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Principally, the low resistance and small arc radius in the EIS-Nyquist plot imply fast charge transfer in the semiconductor, and the experimental results showed that the resistance of Cu-MOF was greatly reduced under light illumination conditions (Figure c). Furthermore, the transient photoluminescence spectra demonstrate the stronger separation efficiency of Cu-MOF for photogenerated electron and hole pairs (Figure d), which further explains the properties of Cu-MOF as a well-performing photocatalyst. , …”
Section: Resultsmentioning
confidence: 74%
“…Furthermore, the transient photoluminescence spectra demonstrate the stronger separation efficiency of Cu-MOF for photogenerated electron and hole pairs (Figure 7d), which further explains the properties of Cu-MOF as a well-performing photocatalyst. 50,51 According to the above experimental results, we attempted to propose a mechanism for the photodegradation of methylene blue by Cu-MOF (Figure 8). When the photon energy irradiated onto Cu-MOF exceeded or equaled to E g (3.29 eV), electron−hole pairs are generated and the excess photoinduced electrons are separated from the valence band and migrate to the conduction band (CB).…”
Section: Synthesis Of Structural Characteristics Of Cu-mofmentioning
confidence: 99%
“…Except for conductive materials, some electrocatalytically active materials, such as metal sulfides and transition metal hydroxide, are widely used to fabricate MOF‐based composites. [ 180,181 ] The synergistic interaction between the additional species and 2D MOF may lead to further enhancement of catalytic properties. The poor HER performances of MoS 2 in basic environment stem from the improper hydroxyl adsorption.…”
Section: D Mof‐based Composites For Electrocatalytic Water Splittingmentioning
confidence: 99%
“…26,27 Furthermore, metal-organic frameworks with ordered organic bridging linkers and inorganic metal nodes promote the well-regulated immobilization of functional organic dye-based ligands into their networks to prevent the aggregation and polymerization of organic dyes. [28][29][30][31] Importantly, the crystalline metal-organic frameworks immobilize photosensitizers and metal ions in high local concentrations to regulate the twisted conjugative junction between the electron-donating and accepting sections, which enable MOFs to markedly heighten the charge-transfer resistance to hamper the futile intramolecular fluorescence quenching. 32,33 Our group has developed a series of triphenylamine-based photoactive metal-organic frameworks to generate radicals by photoreduction.…”
Section: Introductionmentioning
confidence: 99%